Designing “Safer Water.” A Virtual Reality Tool for the Safety and the Psychological Well-Being of Citizens Exposed to the Risk of Natural Disasters - Gamberini, Luciano; Bettelli, Alice; Benvegnù, Giulia; Orso, Valeria; Spagnolli, Anna; Ferri, Michele (Frontiers in Psychology, 2021)
Virtual Reality (VR) is a popular technology to recreate reality-like scenarios, including dangerous ones, in a realistic but safe way. Because of this potential, VR based research has been applied in psychology studies to provide training and education about how to behave in emergencies such as fires, earthquakes, floods, or typhoons. All these different virtual scenarios have been built to observe how people react to emergencies, what behaviors they adopted, what level of stress is generated, and finally, how to increase citizens’ safety. However, there is still little research that shows how Virtual Environment (VE) should be designed to convey appropriate social and psychological "cues" to participants. In this work, we present the result of a series of co-design sessions aiming to bring experts to collaborate in setting up virtual scenarios to increase the quality of life, safety perception and risk awareness in people living in the proximity of a river. Floods are one of the most threatening climate events, and because of climate change, they are expected to become even more frequent. These disasters have a devastating impact on communities, increasing anxiety and stress levels in citizens living close to rivers. We involved relevant stakeholders to design "Safer Water", an immersive, interactive, virtual experience to support citizens in psychologically and behaviorally managing pre and post riverbank breakdown situations. HCI experts, hydrogeological and hydraulic engineers, psychologists and VEs designers took part in affinity diagram and brainstorming activities. Results show how the adopted method was able to generate suitable virtual scenarios, to highlight and classify relevant design requirements, and to find strategies that could improve the quality of life and psychological well-being in "risk-exposed citizens". The discussion includes a set of open-access guidelines derived from the co-design activities, to support the design of VE for the purposes discussed in the paper.